Explaining shifts in systematic risk after merger: Some empirical evidence - G. D.I. Barr; R. C. van den Honert (South African Journal of Business Management, 1988)
In this paper we discuss the change in the beta of an acquiring firm after merger, and examine the unexplained difference between the beta predicted by capital market theory and the beta actually calculated. The analysis is done within two different frameworks, equity beta on the one hand and asset beta (which removes leverage effects from equity beta) on the other. It is found that by using an asset beta approach proportionately more of the beta shifts can be explained by characteristics of the target and acquiring firms than when using the equity beta approach. It is hypothesized that the asset beta approach, which removes the confounding nonlinear effect of debt, constitutes a superior framework to examine shifts in beta.In hierdie artikel bespreek ons die verandering in die sistematiese risiko (beta) van 'n oornemende maatskappy na samesmelting en ons ondersoek die onverklaarde verskil tussen die beta wat deur kapitaalmarkteorie voorspel word en die beta wat werklik bereken word. Die analise word aan die hand van twee verskillende raamwerke gedoen: enersyds volgens aandeelbetas en andersyds volgens batebetas (wat die effek van skuld van die aandeelbeta verwyder). Daar is bevind dat as die batebenadering gebruik word, word eweredig meer van die betaverandering deur die eienskappe van die oorgenome en oornemende maatskappye verduidelik as wanneer die aandeelbetabenadering gebruik word. Daar word veronderstel dat die batebenadering, wat die verwarrende nie-linecre effek van skuld verwyder, 'n meer voortreflike raamwerk is om die veranderings in beta te ondersoek.
Keywords: 650